Batunggu Kubur Tradition: Exploring the Interplay of Spirituality and Social Cohesion in Banjar Society - Wulan Sari; Muhammad Husni; Suryanti (Journal of Islamic History, 2025)
The tradition of grave burying is one of the cultural heritage of the Banjar community in South Kalimantan, full of spiritual and social values. This tradition grew from a combination of pre-Islamic local customs and Islamic teachings deeply rooted in the lives of the community. This grave-burying tradition has the background to strengthen the bonds of brotherhood and show social concern in the form of ta'ziyah and togetherness in times of grief, which makes it unique to study. Several previous studies have examined the phenomenon of the grave burying tradition around the living hadith of the implementation, laws and views of scholars about grave burying. What distinguishes it from this study is that the perpetrators of this tradition are not only Banjar people but also those from outside the area. In addition, this tradition is also a means to reflect on life before death. Based on observations of the socio-cultural realities of the community at the location, this study uses a descriptive qualitative method with data collection techniques based on observation and in-depth interviews with residents, grave guards and RKM (death pillars) around the Amuntai Muslim Residents' Cemetery Complex (HSU) as informants. Based on the results of observations and interviews, several motives for carrying out the grave burying tradition can be obtained. First, the community's belief in the arrival of the angels Munkar and Nakir immediately after the mourners leave the grave is the theological basis of this tradition. Although not explicitly mentioned in the Qur'an or Hadith as mandatory worship, this tradition is considered not to be contrary to Islamic teachings as long as it is carried out with good intentions and does not contain elements of shirk. Second, its implementation involves the activity of reading the Qur'an around the grave for several days after the funeral, with the aim of providing peace for the bereaved family and praying for the deceased to obtain spaciousness in the grave. Third, in the context of values, the grave guardrail reflects Islamic values such as compassion, care, social solidarity, and respect for the corpse. This tradition also shows a form of obedience and community effort in maintaining a spiritual relationship between the living and the deceased. Thus, the grave guardrail is not only a local cultural heritage but also a manifestation of Islamic values in the daily lives of Muslims in South Kalimantan and its surroundings. REFERENCES Abidin. (2023, August 23). Interview [Personal communication]. Ahmad, H. (2023, July 23). Interview [Personal communication]. Angkat, C. A. br, Lubis, M. Z. H., & Ginting, L. D. C. U. (2024). KARO'S THREATENED CULTURAL HERITAGE: EFFORTS TO PRESERVE AND DEVELOP THE TEMBUT-TEMBUT MASK TRADITION. Journal of Scientific Horizons, 3(8), Article 8. Arifin, M. N., Wahyuni, N., & Asrori, M. (2024). Tahlilan Tradition of the Suka Jaya Village Community in the Perspective of Islamic Education. Arfannur: Journal of Islamic Education, Volume 5, Number 1, 57-65. https://doi.org/10.24260/arfannur.v5i1.1710 Asrori, A. (2022). THE TRADITION OF TAHLILAN AND GRAVE PILGRIMAGE FROM THE PERSPECTIVE OF CULTURAL PHILOSOPHY: Descriptive Study in Beringin Village, Campang Jaya Village [Thesis]. UIN Raden Intan Lampung. Azzahra, S. (2025). AN ANALYSIS OF THE LAW OF THE GRAVE GUARDING TRADITION IN THE BANJAR COMMUNITY. Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory (IJIJEL), 3. BPS Palangka Raya City. (2024). BPS Palangka Raya City (1-22). BPS Palangka Raya City. Buseri, K. (2012). THE SULTANATE OF BANJAR AND THE IMPORTANCE OF ISLAMIC PROSELYTIZATION. AL-BANJARI Scientific Journal of Islamic Sciences, Vol. 11, No. 2, 221-230. https://doi.org/10.18592/al-banjari.v11i2.457 Caswito, Muarif, Y. Z., & Aziz, A. (2024). Islamic Law Reform: Achieving Grace through Tahlil & Tawasul. Vol. 6 No.2, 241-262. https://doi.org/10.20885/PLR.vol6.iss2.art5 Erawati, D. (2017). THE ROLE OF SOCIALIZATION OF THE VALUE OF TOGETHERNESS IN AN EFFORT TO OVERCOME RELIGIOUS CONFLICT IN COMMUNITY LIFE IN THE CITY OF PALANGKA RAYA. Palita: Journal of Social Religion Research, Vol.2 No.1, 1-112. https://doi.org/10.24256/pal.v2i1.63 Farhan, M. (2023, July 23). Interview [Personal communication]. Geography and Climate of Palangka Raya City Government. (2021). https://palangkaraya.go.id/selayang-pandang/geografis/ Hadi, M. M. (2022). SOCIAL MODAL IN PRESERVING THE COUNTRY OF MULTICULTURAL COMMUNITY (Study of Religious Harmony in Pabuaran Village, Gunung Sindur District, Bogor Regency) [Thesis]. UIN Syarif Hidayatillah. Hatimah, H., Emawati, & Husni, M. (2021). Tahlilan Tradition of Banjar Community in Pahandut Sub-district, Palangka Raya City. Syams: Journal of Islamic Studies, Volume 2 Number1. http://e-journal.iain-palangkaraya.ac.id/index.php/syams Hendraswati, Asnaini, & Sulistyorini, P. (2006). Pahandut: A Review of Socio-Political History. West Kalimantan Cultural Value Preservation Center (BPNB), Ministry of Education and Culture. Indriani, A. N. (2022). TRADITION OF DEATH CEREMONY REVIEWED FROM ISLAMIC VALUES IN THE PERSPECTIVE OF SIMBOLIC INTERACTION IN THE MAJU XII COMMUNITY OF WEST LAMPUNG [Thesis]. UIN Raden Intan Lampung. Ishaac, M., & Mukarram, M. L. (2024). Islamic Education Values in Batunggu Kubur Tradition in Lok Baintan Village, Sungai Tabuk District. Tamadduna: Journal of Civilization, 67-76. https://doi.org/10.29313/tamadduna.v1i2.5037 Jannah, M. (2014). Living Hadith in the Grave Guarding Tradition of the Banjar Community of Hulu Sungai Tengah Regency, South Kalimantan. ESENSIA: Journal of Ushuluddin Sciences, 15(1), Article 1. https://doi.org/10.14421/esensia.v15i1.763 Junaidi. (2017). THE BATUNGGU KUBUR TRADITION ACCORDING TO THE OPINIONS OF NAHDLATUL 'ULAMA (NU) AND MUHAMMADIYAH 'ULAMA IN MARABAHAN [Thesis]. IAIN Antasari Banjarmasin. Kapindo, R. A. (2023). THE TRADITION OF CONDOLENCE AND RELIGIOUS HARMONY IN THE EAST PRINGSEWU VILLAGE, KAB. PRINGSEWU [Thesis, UIN Raden Intan Lampung]. https://repository.radenintan.ac.id/22970/1/SKRIPSI%20BAB%201%265.pdf?utm_source=chatgpt.com Ministry of Education and Culture (1986). Traditional Death Ceremony of South Kalimantan. https://repositori.kemdikbud.go.id/27755/ Khairi, M. M. (2023). Recitation of the Qur'an in the Batunggu Kubur Tradition for the People of Palangka Raya City [Thesis, UIN Antasari Banjarmasin]. http://idr.uin-antasari.ac.id/id/eprint/24841 Khalida, A., Aprianti, Y., & Azkia, L. (2022). Gravediggers in Cakeru Village, North Amuntai District, Hulu Sungai Utara Regency. JTAMPS: Journal of Final Project of Sociology Education Students, Vol. 2 No. 2. https://ppjp.ulm.ac.id/journals/index.php/jtamps/index Miles, M. B., Huberman, A. M., & Saldana, J. (2018). Qualitative Data Analysis: A Methods Sourcebook (4th ed.). SAGE. Nadhiroh, W. (2019). THE RELIGIOUS REASONING OF THE BANJAR COMMUNITY: FROM MYSTICAL-REALIST TO TRADITIONALIST-CRITICAL. AL-BANJARI Scientific Journal of Islamic Sciences, Vol.18, No.2, 246-273. https://doi.org/10.18592/al-banjari.v18i2.3003 Noor, M. I. (2011). ISLAMIC REASONING OF URANG BANJAR. Al-Banjari, Vol. 10, No.2, 145-164. Nuraini, & Jannah, W. (2020). The Tradition of Reciting the Qur'an in Graveyards in Indonesian Society. Tafse: Journal of Qur'anic Studies, Vol. 5, No.2, 64-81. Ravens. (2024). The Tradition of Reciting the Qur'an at Batunggu Kubur in the Community of Murung Raya Village, South Banjarmasin District (Living Qur'an Study) [State Islamic University (UIN) Antasari Banjarmasin]. https://idr.uin-antasari.ac.id/26057/ Rahmadi. (2022). RELIGION AND CULTURE OF THE BANJAR PEOPLE: A Thematic Overview of Religion and Locality Research Results (1st ed.). ZAHIR PUBLISHING. https://idr.uin-antasari.ac.id/20779/1/Agama%20dan%20Budaya%20Masyarakat%20Banjar_Rahmadi_rev-sb.pdf Rahman, G., Husin, & Rusydi, A. (2021). THE TRADITION OF GRAVE GUARDING IN THE BANJAR COMMUNITY. ISoLEC Proceedings, 5(1), Article 1. Ramadan, I. (2022). Study of Living Hadith on the Khataman al-Qur'an Tradition over Graves in North Padang Lawas: Study of Living Hadith on the Khataman al-Qur'an Tradition over Graves in North Padang Lawas. Journal of Living Hadith, 7(2), Article 2. https://doi.org/10.14421/livinghadis.2022.4277 Sarifudin, L. (2023, August 12). Interview [Personal communication]. Satimin. (2021). Philosophical Values in Commemorating the Day of Death Ceremony in Javanese Tradition Viewed from Social Aspects (Study in Air Banai, Hulu Palik Subdistrict, North Bengkulu Regency. 6 No. 1, 43. Septiana, R. A. E. (2018). THE POLITICS OF DEATH IN PRAXIS INTERPRETATION, A STUDY OF THE POLITICAL CONSTELLATION OF FAKEM PALEMBANG DARUSSALAM IN THE PALEMBANG CITY ELECTION ERA. 1. Sunarno, A., Firman, Ikbal, A., & Indrawati, L. (2023). EFFORTS TO MINIMIZE CASES OF INTOLERANCE IN THE ESTABLISHMENT OF PLACES OF WORSHIP FOR THE CREATION OF SOCIAL COHESION IN MULTICULTURAL COMMUNITIES IN CENTRAL KALIMANTAN. Journal of Paris Langkis, 3 Number 2, 93-100. https://doi.org/10.37304/paris.v3i2.8719 Syukri, A. (2011). The Practice of Giving Rewards to the Dead in the Perspective of Fiqh Muqaran (A Comparative Study Between the Opinions of Mazhab Ulama who Support and Reject it) [Thesis, UIN Sultan Syarif Kasim Riau]. http://repository.uin-suska.ac.id/id/eprint/326 Tahir, A. (2019). Textbook of Organizational Behavior. Nilacakra. Umilati, D., Iqbal, M., Husni, M., Anggraeni, N. N., & Romdhoni, A. R. (2023). SAINT OF SOUTH KALIMANTAN: BANJAR PEOPLE'S PILGRIMAGE TO THE TOMB OF SHEIKH NAFIS IDRIS AL-BANJARI. Journal of Religious and Community Studies, Vol. 19, No. 2, 150-161. https://doi.org/10.23971/jsam.v19i2.7522 Death Ceremonies in Banjar Society (South Kalimantan). (t.t.). Death Ceremony in Banjar Society (South Kalimantan). Retrieved May 29, 2025, from https://uun-halimah.blogspot.com/2008/06/upacara-kematian-pada-masyarakat-banjar.html W, K. (2017). Motivation of the Palangka Raya Community in Implementing the Tradition of Waiting for Graves in the Review of Islamic Law. Journal of Religious and Community Studies, 11(2), 174. https://doi.org/10.23971/jsam.v11i2.436 Waluya, B. (2007). Sociology: Exploring social phenomena in society. PT Grafindo Media Pratama. https://books.google.com/books?hl=en&lr=&id=pGxmsW9Emc0C&oi=fnd&pg=PA4&dq=info:HyTp5FRpc8J:scholar.google.com&ots=0PnigQlthN&sig=Jjw7yKB5BYTMcFrJGuNY9olGl6c Yusof, M. Y. S., & Ramli, M. A. (2021). Local Wisdom of Tahlīland Tunggu KuburPractices in Death Custom among the Malaysin Malaysia. UMRAN: International Journal of Islamic and Civilizational Studies, Vo.8 No.2, 39-48. https://doi.org/10.11113/umran2021.8n2.396